Tissue Doppler vs. conventional parameters for diagnosis of tamponading pericardial effusion: a cross-sectional study in tertiary referral center - Ahmed Behairy; Amira Esmat El Tantawy; Asmaa Mahmoud Hamed; Antoine AbdelMassih; Sara Tarek (SpringerOpen, 2023)
Abstract Background Conventional signs of tamponade include right ventricular and atrial collapse and respiratory variation in mitral inflow velocities. Despite being reliable, they are qualitative in nature and are not well correlated with clinical signs of deterioration or improvement. Tamponade is invariably preceded and associated with diastolic dysfunction, and tissue Doppler imaging (TDI) can help in early detection of it, earlier than conventional signs. For this purpose, 36 patients presenting with pericardial effusion have been subjected to echocardiography, including effusion dimensions, presence or absence of routine signs of tamponade and TDI-derived LV and RV E/E' ratios, as well as clinical signs of tamponade to test the diagnostic accuracy of echocardiographic parameters against them. Results Right atrial and ventricular collapse were the least accurate in the detection of tamponade, while effusion dimension > 14 mm was the most accurate among conventional parameters to point toward tamponade. RV and LV diastolic dysfunction as evidenced by E/E' ratio showed 100% sensitivity in predicting tamponade, while LV E/E' ratio showed the highest specificity (100%) in the same context. The higher diagnostic accuracy of LV E/E' ratio might be also related to the presence of chronic kidney disease patients, with an already jeopardized LV function. Conclusions TDI technology is now available in most of the portable echocardiography machines and can serve as part of point-of-care echocardiography in the early detection of cardiac tamponade and in decision making for pericardiocentesis. Larger studies can help in consolidating the impression driven from our small-scale cross-sectional study.